THEMATIC PROGRESSIONS OF THE 2015 TEFLIN ARTICLE ABSTRACTS IN APPLIED LINGUISTICS - Reski Oktaviani Yuned; Azwandi .; Arono . (Universitas Bengkulu, 2016)
Coherence is one of the characteristic of good academic writing, including abstract that represent the whole content of research article in order to be able to show what messages want to be expressed in the abstract. This study investigated the English abstract TEFLIN in applied linguistisc written by Indonesian speaker in its coherence by analyzing the theme and rheme. This study focuses on (1) identifying the theme which are dominantly used in 2015 TEFLIN article abstracts written by non-native speaker of English (2) identifying thematic progressions which are dominantly used in 2015 TEFLIN article abstracts written by non-native speaker of English (3) finding out coherences’ quality of the research article abstract section in 2105 TEFLIN article abstracts in applied linguistic based on thematic progression. This study was designed by using descriptive qualitative. The results show that the type of theme dominantly used in 2015TEFLIN article abstracts written by non-native speaker of English is topical theme, not all non-native speakers of English use textual theme, and just a few of them useinterpersonal theme. In addition, Zig Zag pattern in thematic progression is dominantlyused then followed by reitaration theme, and the last Multiple (Split) pattern, none of the abstracts use Derived TP pattern. Most of the research article abstract section in TEFLIN abstracts in applied linguistic have fair quality, just a few included to less quality, none of them was catagorized as good and poor quality. It can be concluded that English abstracts of TEFLIN in applied linguistisc written by Indonesian speakers can be catagorized as good abstract based on their coherence.